2017
DOI: 10.1089/scd.2016.0234
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Induces Proliferation of Hair Follicle-Derived Mesenchymal Stem Cells Through Epidermal Growth Factor Receptor-Mediated Activation of ERK and AKT Signaling Pathways Associated with Upregulation of Cyclin D1 and Downregulation of p16

Abstract: The maintenance of highly proliferative capacity and full differentiation potential is a necessary step in the initiation of stem cell-based regenerative medicine. Our recent study showed that epidermal growth factor (EGF) significantly enhanced hair follicle-derived mesenchymal stem cell (HF-MSC) proliferation while maintaining the multilineage differentiation potentials. However, the underlying mechanism remains unclear. Herein, we investigated the role of EGF in HF-MSC proliferation. HF-MSCs were isolated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
53
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 47 publications
9
53
0
1
Order By: Relevance
“…Furthermore, we demonstrated that inhibition of ERK/MAPK pathway could promote the senescence of endosteal osteoprogenitors and block the survival and proliferation ability of osteoprogenitors induced by EGF treatment. This is consistent with a recent report that EGFR signaling promotes proliferation of hair follicle-derived mesenchymal stem cells through ERK1/2 and suppresses the expression of the p16 INK4a (35). Therefore, advancing age is associated with a decrease in EGFR/ERK signaling whereby endosteal osteoprogenitors undergo senescence, leading to decreased endosteal bone formation and cortical bone degeneration.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we demonstrated that inhibition of ERK/MAPK pathway could promote the senescence of endosteal osteoprogenitors and block the survival and proliferation ability of osteoprogenitors induced by EGF treatment. This is consistent with a recent report that EGFR signaling promotes proliferation of hair follicle-derived mesenchymal stem cells through ERK1/2 and suppresses the expression of the p16 INK4a (35). Therefore, advancing age is associated with a decrease in EGFR/ERK signaling whereby endosteal osteoprogenitors undergo senescence, leading to decreased endosteal bone formation and cortical bone degeneration.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study using hair follicle-derived mesenchymal stem cells found that EGF significantly increased proliferation as well as phosphorylation of EGFR, ERK, and AKT in a time- and dose-dependent manner, increased cyclin D1 levels, and shifted cells from G1 to the S and G2 phases. In addition, AG1478, LY294002, or U0126 prevented EGF-induced cell proliferation and reduced p-EGFR, p-AKT, and p-ERK1/2 expression [35]. Together with our findings, these data suggest that the overall pattern of EGFR activities in ES resembles that found in mesenchymal stem cells from healthy donors.…”
Section: Discussionsupporting
confidence: 82%
“…Another limitation is that HFT differentiation was only analyzed using Oil Red O staining, not differentiation markers or fluorescence-activated cell sorting analysis. Additionally, previous studies have reported other potential molecular pathways that may be associated with the proliferation (33)(34)(35)(36)(37) and differentiation of HFTs, including the Wnt signal transduction pathway, forkhead box P1-mediated oxidative stress and epidermal growth factor receptor/extracellular signal-regulated kinases/AKT, c-Jun N-terminal kinases/c-Jun and TGF-β pathways (38). The present study only investigated the PI3K/AKT signaling pathway in HFTs.…”
Section: Discussionmentioning
confidence: 90%